2022
DOI: 10.1261/rna.079129.122
|View full text |Cite
|
Sign up to set email alerts
|

Vault RNA1–1 riboregulates the autophagic function of p62 by binding to lysine 7 and arginine 21, both of which are critical for p62 oligomerization

Abstract: Cellular processes can be regulated at multiple levels, including transcriptional, post-transcriptional and post-translational mechanisms. We have recently shown that the small, non-coding vault RNA1-1 negatively riboregulates p62 oligomerisation in selective autophagy through direct interaction with the autophagic receptor. This function is highly specific for this Pol III transcript, but the determinants of this specificity and a mechanistic explanation of how vault RNA1-1 inhibits p62 oligomerisation are la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…Mutational analysis revealed that the disruption of this short domain on vtRNA1-1, similarly to the vault RNA KO, increases apoptosis. This short stretch is located in the central region of the RNA, where the secondary structure features a single-stranded loop region and a stem-loop [ 48 , 58 ]. This domain has been shown to bind to p62 (sequestosome1 protein SQSTM1) [ 58 ] and is possibly also the anchor point for other vtRNA1-1 interacting proteins, although the binding partners of the vault RNA orchestrating apoptosis have not been uncovered yet.…”
Section: Vtrna1-1: Contributions To Cell Proliferation and Tumorigenesismentioning
confidence: 99%
See 2 more Smart Citations
“…Mutational analysis revealed that the disruption of this short domain on vtRNA1-1, similarly to the vault RNA KO, increases apoptosis. This short stretch is located in the central region of the RNA, where the secondary structure features a single-stranded loop region and a stem-loop [ 48 , 58 ]. This domain has been shown to bind to p62 (sequestosome1 protein SQSTM1) [ 58 ] and is possibly also the anchor point for other vtRNA1-1 interacting proteins, although the binding partners of the vault RNA orchestrating apoptosis have not been uncovered yet.…”
Section: Vtrna1-1: Contributions To Cell Proliferation and Tumorigenesismentioning
confidence: 99%
“…This short stretch is located in the central region of the RNA, where the secondary structure features a single-stranded loop region and a stem-loop [ 48 , 58 ]. This domain has been shown to bind to p62 (sequestosome1 protein SQSTM1) [ 58 ] and is possibly also the anchor point for other vtRNA1-1 interacting proteins, although the binding partners of the vault RNA orchestrating apoptosis have not been uncovered yet. An initial mechanistic hint was recently published, suggesting a possible direct interaction of mouse vtRNA with MEK1, thus stimulating MAPK signaling and synaptogenesis [ 59 ].…”
Section: Vtrna1-1: Contributions To Cell Proliferation and Tumorigenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Mutational assays targeting this RNA segment have shown an increase in apoptosis in HeLa cells treated with the drug chloroquine and subjected to nutrient deprivation using starvation medium [ 128 ]. Moreover, this domain has been shown to interact with p62, a protein involved in autophagy [ 138 ]. As a result, it may also serve as a central point for interactions with other RBPs (Fig.…”
Section: Vault Rnas In Other Cellular Processesmentioning
confidence: 99%
“…The stem-loop structure in the apical region of vtRNA 1-1 enhances resistance to apoptosis by modulating the PI3K/Akt and ERK1/2 MAPK signaling pathways, with critical nucleotides for apoptosis resistance encircled in blue [ 87 , 127 ]. Additionally, vtRNA 1-1 inhibits autophagy by preventing p62 oligomerization, and the relevant nucleotides for this proposed role are encircled in red [ 138 , 143 ]. Moreover, vault particles can interact with SQSTM1/p62, contributing to the enhancement of the vault-phagy process [ 141 ] …”
Section: Vault Rnas In Other Cellular Processesmentioning
confidence: 99%